Life lessons from the great books - Fears, J. Rufus, 1945-2012.; Teaching Company (Chantilly, VA : Teaching Co., 2009)
This course explores six themes that every one of us has experienced or will experience: the unconquerable human spirit; youth, old age, and all that is between; romance and love; adventure and courage; laughter and irony; and patriotism.
disc 5. Lectures 25. Aristophanes, comedies ; Lecture 26. Menaner, The grouch ; Lecture 27. Machiavelli, La mandragola ; Lecture 28. Erasmus, In praise of folly ; Lecture 29. Thomas More, Utopia ; Lecture 30. George Orwell, Animal farm ; disc 6. Lecture 31. Josephus, History of the Jewish War ; Lecture 32. Joseph Addison, Cato ; Lecture 33. George Washington, farewell address ; Lecture 34. Abraham Lincoln, George Patton, war ; Lecture 35. Theodore Roosevelt, an autobiography ; Lecture 36. The wisdom of great books.
"Literature & English language"--Container.
In 1 container with course guidebook separate..
Professor J. Rufus Fears, lecturer, University of Oklahoma.
DVD.
Keywords: Literature; Philosophy in literature; Filmed lectures; Educational films